Modelling and optimization of carbon dioxide sequestration potential of carbide slag waste - Manisha Sukhraj Kothari; Ashraf Aly Hassan; Amr El-Dieb; Hilal El-Hassan (Case Studies in Chemical and Environmental Engineering, 2025)
Mineral carbonation (MC) of industrial wastes has gained significant attention as a promising approach for reducing carbon dioxide (CO2) emissions. This study investigates the wet-phase MC of carbide slag waste at realistic conditions for CO2 capture and storage. Response Surface Methodology with a central-composite design was employed for optimization and modeling for wet-phase MC of carbide slag waste. Five operational parameters namely temperature, pressure, relative humidity, liquid-to-solid (L/S) ratio, and CO2 loading rate were analyzed for their individual and interactive effects on CO2 capture capacity and the reaction kinetics. Further, quadratic models were developed to predict CO2 capture capacity and time required for 50 % carbonation conversion (time50). The results revealed that the most influential factor was pressure followed by the L/S ratio for CO2 capture capacity. While time50 was majorly influenced by the CO2 loading rate and pressure. The quadratic models for CO2 capture capacity and time50 have an R2 value of 0.9863 and 0.9986, respectively. Moreover, the results predicted from the models for both responses were closely aligned with the experimental results. The optimized conditions yielded a maximum CO2 capture capacity of 11.9 mol kg−1 at 10 bar pressure, 65 °C, in the presence of 0.2 L/S ratio and 75 % relative humidity in 121 minutes, where 50 % conversion occurs in the first 52 minutes. In conclusion, wet-phase MC of carbide slag represents a promising approach to address both industrial waste utilization and CO2 reduction. The high CO2 capture capacity achieved under various experimental conditions demonstrates carbide slag as a viable candidate for large-scale CO2 capture applications. Furthermore, techno-economic analysis and scalability assessments will be crucial in advancing this approach to industrial relevance.